Baby boomers, their elders and the public library - Cavanagh, Mary; Robbins, Wendy (Université d'Ottawa | University of Ottawa, 2012)
Purpose – Canada's aging population is expected to have an impact on all public institutions; for public libraries, the emergence of a large, multi‐generational user group of older adults challenges the current paradigm of services to seniors. The purpose of this paper is to report on the reflections of a small sample of baby boomers and how the public library‐as place contributes to their caring relationships with their elders. Design/methodology/approach – This study examined a subset of baby boomer library patrons who are in caring relationships with elders. The study is theoretically framed by the ethic of care and emerging theories of library‐as‐place grounded in human geography and sociology. An instrumental case study of seven carers in an urban Canadian city was conducted, using long form interviews. Findings – Findings suggest that while these baby boomer respondents value their libraries deeply, there is potential to create services and practices more attuned to the needs of older adults who are in relationships with elders. Research limitations/implications – As a single case of a small sample of baby boomers, this study is limited by its size, scope and geography. The direct voices of the elders could not practically be incorporated into this study and should be considered in future research. Originality/value – This study offers an alternate framework to library‐as‐place studies based on a specific profile of “older adult” library users. It examines the library needs and uses of a small but rapidly growing sector of many public library communities. Older adults can be seen by libraries as two distinct demographic groups – the very old (elders) and their younger peers (baby boomers).
Keywords: Baby boomers; Ethics of care; Public libraries